Capacity enhancement in indoor environment by hybrid combiner circuit of multinetworks operator - W. Mohamad, Wan Norsyafizan; Sarnin, Suzi Seroja; Yusof, Mohd Yusdee; S Abdul Kadir, Ros Shilawani; Mad Tan, Mohd Nor; Zainul Azlan, Norsinnira; Baharudin Zamani, Zarina (Semnan University, 2021)
This study focuses on providing a solution for a mobile service provider with Multi Network Operators (MNOs) to provide an excellent service attended by thousands of Mobile Subscribers (MS) at Nasional Bukit Jalil Kuala Lumpur Stadium in Malaysia using a single multi-beam antenna via a hybrid circuit. The Hybrid Combiner (HC) is the solution used to combine multiple MNOs in order to minimize space and cost while maintaining the aesthetic value of the national stadium. During a significant incident, MS users may encounter difficulties accessing the service due to network congestion. In this case, MNOs will need to add capacity to meet the demand for data transmission and voice call transactions. In the current situation, MS users have received poor service because they are unable to connect to the internet or make phone calls while attending a major event at a stadium. MS users will be able to access the network and enjoy live feeds via Facebook (FB) and other software applications without delay or interruption, as well as voice call congestion, following the implementation of the proposed solution. Using the Planning Methods, the results of the proposed solution will be compared to the results of the Walk Test and the coverage simulation analysis. Data statistics obtained from MNOs will explain the solution’s effectiveness in terms of signal quality level, with the Signal to Noise Ratio (SINR) recorded at -95 dBm below the threshold of -85 dBm to prevent interference with MS users. The Resource Block (RB) Utilization shows that all sectors are utilized at less than 70% of total available capacity, indicating that the congestion level is manageable and MS users can access the network without interruption. A key factor in the proposed study, known as Hybrid Combiner Circuit of Multi Network Operator for Capacity Enhancement Solution in Indoor Environment, is fast deployment, low maintenance, and a shared solution between MNOs.